Shaun the Sheep. Little sheep of horrors [videorecording (DVD)] - Sadler, Christopher, 1970- (Lions Gate Entertainment, Inc., 2016)
"What's black and white and goes bump in the night? Don't be scared -- it's your woolly friend, Shaun the Sheep! Join Shaun as he leads his fearless flock through six adventures. Freaky farm noises and sleepwalking sheep are only a few of the weird and wonderful surprises waiting for Shaun and his barnyard pals as they creep, sneak, and make mayhem in this laugh-filled collection." --Publisher's description.